Species Distribution of Euglossini Bees (Hymenoptera: Apidae) at an Altitudinal Gradient in Northern Santa Catarina - Enderlei Dec; Isabela Alves dos Santos (Sociobiology, 2019)
Euglossini bees are found from southern USA to Central Argentina and southern Brazil. Variations in latitude and altitude can influence the distribution of these bees. This study focused in recognizing the Euglossini species in northern Santa Catarina state, evaluating the distribution over the gradient between sea level and 800 meters altitude. The bees were collected in six locations, between Spring and Summer from 2013 to 2015, using cotton balls containing the following odor baits: benzyl benzoate, 1,8 cineole, eugenol, menthol and vanillin. A total of 794 bees were sampled, belonging to 10 different species, including a possible new species. In terms of abundance Eufriesea Cockerell, 1908 (4 species) accounted for 552 individuals, followed by Euglossa Latreille, 1802 (5 species) with 218 and Eulaema Lepeletier, 1841 (2 species) 24 individuals.  Five species were not found above altitude of 400 meters. Eufriesea violacea Blanchard, 1840, Euglossa annectans Dressler, 1982, and Eulaema nigrita Lepeletier, 1841 were the only species found in every location along the altitudinal gradient, but their abundance declines toward higher altitudes. The results surpassed the known orchid bee species for Santa Catarina state from 9 to 14 and confirmed the expected tendency of richness and abundance reduction toward the highlands. tendency of richness and abundance reduction toward the highlands.